Docking Simulations of G-Protein Coupled Receptors Uncover Crossover Binding Patterns of Diverse Ligands to Angiotensin, Alpha-Adrenergic and Opioid Receptors: Implications for Cardiovascular Disease and Addiction - Harry Ridgway; Graham J. Moore; Laura Kate Gadanec; John M. Matsoukas (Biomolecules)
Recent bioassay studies have unexpectedly supported the high (computationally predicted) binding affinities of angiotensin receptor blockers (ARBs) at α-adrenergic receptors (αARs) in isolated smooth muscle. Computational predictions from ligand docking studies are consistent with very low concentrations of ARBs (e.g., sartans or bisartans) that partially reduce (20–50%) the contractile response to phenylephrine, suggesting that some ARBs may function as partial inverse agonists at αARs. Virtual ligand screening (docking) and molecular dynamics (MD) simulations were carried out to explore the binding affinities and stabilities of selected non-peptide ligands (e.g., ARBs and small-molecule opioids) for several G-protein coupled receptor (GPCR) types, including angiotensin II (AngII) type 1 receptor (AT1R), α1AR, α2AR, and μ-(µOR) and ժ-opioid receptors (ժOR). Results: All ligands docked preferentially to the binding pocket on the cell surface domain of the GPCR types investigated. Drug binding was characterized by weak interactions (hydrophobic, hydrogen bonding, pi-pi) and stronger ionic and salt-bridge interactions (cation-pi and cation-anion interactions). Ligands specific to each GPCR category showed considerable cross-binding with alternative GPCRs, with small-molecule medications appearing less selective than their peptide or ARB functional equivalents. ARBs that exhibit higher affinities for AT1R also demonstrate higher affinities for µORs and ժORs than opiate ligands, such as fentanyl and naltrexone. Moreover, ARBs had a higher affinity for αARs than either alpha agonists (epinephrine and phenylephrine) or inhibitors (prazosin and doxazosin). MD simulations of membrane-embedded ARB-GPCR complexes proved stable over nanosecond time scales and suggested that some ARBs may behave as agonists or antagonists depending on the GPCR type. Based on the results presented in this and related investigations, we propose that agonists bind to the resting A-site of GPCRs, while inverse agonists occupy the desensitizing D-site, which partial agonists like morphine and fentanyl share, contributing to addiction. ARBs block both AngII and alpha receptors, suggesting that they are more potent antihypertensive drugs than ACE inhibitors. ARBs have the potential to inhibit morphine tolerance and appear to disrupt receptor desensitization processes, potentially by competing at the D-site. Our results suggest the possible therapeutic potential of ARBs in treating methamphetamine and opiate addictions.